2011
DOI: 10.1016/j.ejcts.2010.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Positive cultures from cardiopulmonary bypass: prevalence and relevance regarding postoperative infection

Abstract: Positive cultures from both CPB priming fluid and CPB blood samples were not a rarity and mainly involved skin bacteria, arguing that contamination may have played a role. The risk of postoperative infection within 30 days after surgery was not increased in CPB-culture-positive patients. Therefore, no evidence was found to support routine culturing of CPB samples in patients undergoing cardiothoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The group with CBP duration of up to 85 minutes presented a higher percentage for this complication (25%). A recent research on the epidemiology of CBP fluid and blood sample cultures demonstrated that 5.7% of the patients presented fever of unknown origin during the postoperative period, without any significant difference between patients with positive or negative cultures, and no association was established with CBP duration either (26) . Some complications, like bleeding, hemothorax and pneumothorax, only appeared in the group with CBP duration of more than 85 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…The group with CBP duration of up to 85 minutes presented a higher percentage for this complication (25%). A recent research on the epidemiology of CBP fluid and blood sample cultures demonstrated that 5.7% of the patients presented fever of unknown origin during the postoperative period, without any significant difference between patients with positive or negative cultures, and no association was established with CBP duration either (26) . Some complications, like bleeding, hemothorax and pneumothorax, only appeared in the group with CBP duration of more than 85 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…No correlation between positive cultures in the blood from the CPB circuit and postoperative infection have been established in previous studies 65,156 and were also not found in study IV. Positive cultures and postoperative infections needs to be evaluated in larger studies.…”
Section: Heparin Reversal With Protaminementioning
confidence: 71%
“…Live bacteria found in the CPB blood on the other hand are mainly those colonizing the patients own skin 67 so assumingly they also are introduced to the blood through the operation field. No association between positive cultures and an increased postoperative risk for infection has been found 65 .…”
Section: Endotoxemia and Bacteremiamentioning
confidence: 98%
See 2 more Smart Citations